Pengaruh Kombinasi Ultrasound Dan Mc Kenzie Terhadap Penurunan Nyeri Pada Pasien Nyeri Punggung Bawah Miogenik - Arief Efendi; Nurul Halimah (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Objective: Myogenic low back pain is myogenic low back pain is pain associated with spasm of the back muscles, tendons, and ligaments usually due to overexertion. The effect of ultrasound and mc kenzie combination on pain reduction in myogenic low back pain patient Methods: This study has 20 respondents using a sampling technique that is purposive sampling. This research design uses a quasi-experimental type with a one group pretest and posttest approach. Carried out for 4 weeks with 2 times a week.Results: The effect of ultrasound and mc kenzie combination on pain reduction in myogenic low back pain patient with p-value = 0.001 (p<0.05).Conclusion: This research can be concluded that the combination of ultrasound and mc Kenzie can reduce pain in myogenic low back pain patients.Keywords: Ultrasound, Mc Kenzie, Nyeri Punggung Bawah